Modern strategies for the gastric cancer prevention - Dmitry S. Bordin; Karine A. Nikolskaya; Margarita V. Chebotareva; Igor E. Khatkov (Терапевтический архив)
Gastric cancer (GC) is one of the top five cancer morbidity and mortality rates in the Russian Federation and worldwide. Currently, there is a decrease in gastric cancer incidence, which is associated with a decrease in the prevalence of Helicobacter pylori infection. However, due to changes in the population structure and increased life expectancy, the absolute number of gastric cancer cases and mortality are expected to increase. GC is a consequence of long-term chronic gastritis. At least 90% of gastric cancers are caused by H. pylori. Reducing the incidence and mortality from GC is achievable with a reasonable combination of 2 strategies: primary prevention based on the detection and eradication of H. pylori, and secondary prevention, which is based on endoscopic screening of early GC and the formation of high-risk groups for cancer development and their subsequent endoscopic observation.